Single-cell profiling uncovers PTPRG-driven stemness in malignant plasma cells and signatures of treatment failure in multiple myeloma - Tan, Jiewen; Zhong, Jinman; He, Yueping; Xu, Yunman; Chen, Chang; Xiong, Dan (Frontiers in Immunology, 2025)
BackgroundMultiple myeloma (MM) is characterized by extensive intratumoral heterogeneity and complex interactions within the bone marrow microenvironment, yet the cellular and molecular drivers of treatment resistance remain poorly defined. Protein tyrosine phosphatase receptor gamma (PTPRG) has emerged as a candidate tumor suppressor in various malignancies by antagonizing proliferative and survival signaling, but its functional and prognostic relevance in MM has not been established.MethodsWe analyzed 103,171 single‐cell transcriptomes from 18 MM samples (10 optimal responders [OR] and 8 suboptimal responders [SOR] to bortezomib–melphalan–prednisone) to investigate cell‐type composition, malignant plasma cell subclusters, and tumor–microenvironment crosstalk. InferCNV was used to distinguish malignant plasma cells, which were further reclustered and correlated with bulk prognostic phenotypes. Differential expression, pathway enrichment, transcription‐factor activity, pseudotime trajectory, and ligand–receptor interaction analyses were performed. Finally, bulk datasets (GSE9782, GSE2658, MMRF-CoMMpass) and in vitro knockdown assays in U266 and NCI-H929 cells were used to validate the prognostic and functional role of PTPRG.ResultsEleven major cell types were annotated, with plasma cells, T/NK cells, and CD14+ monocytes predominating; SOR samples exhibited an expanded plasma‐cell fraction and reduced T/NK, CD14+ monocyte, pre-B, and HSPC populations. Among 35,944 malignant plasma cells, five subclusters were defined; one subcluster (MalPlasma3) was enriched in SOR samples and harbored 93.1% of cells associated with poor survival. MalPlasma3 and “worse‐survival” cells showed activation of stemness, E2F/MYC targets, and G2M checkpoint pathways, driven by transcription factors E2F8, E2F7, FOXM1, E2F1, and TIMELESS. Pseudotime analysis revealed a bifurcating differentiation toward a resistant phenotype, accompanied by upregulation of cell‐cycle and proliferation modules. In the OR group, enhanced cytotoxic features in NK, effector, and naïve T cells, along with IGF1–IGF1R and IFNG–IFNGR signaling, suggested a supportive microenvironment. In contrast to the known role as a tumor suppressor in solid and hematologic cancers, our integrative analyses identified PTPRG among seven stemness‐related genes upregulated in MalPlasma3 and poor‐survival cells, which was echoed in the observed reduced cell viability and increased apoptosis in MM cell lines following siRNA‐mediated PTPRG knockdown.ConclusionsThis single‐cell multi‐omic dissection implicates a proliferative, stem‐like MalPlasma3 subcluster and identified PTPRG as a key mediator of drug resistance and poor outcome in MM, offering novel prognostic biomarkers and therapeutic targets.